Effects of COVID-19: Hopelessness and Death Anxiety in Patients Aged 65 and Over - Ozalp, Cemal; Avsar, Guelcin; Sogucak, Suna (Springer, 2025)
It is thought that age is an important factor in hopelessness and death anxiety, particularly in older adults during an epidemic disease like COVID-19, where death rates are high. This study was conducted to examine hopelessness and death anxiety in patients aged 65 and over who were diagnosed with COVID-19. The study was conducted between March and April 2021 in a pandemic hospital specially designated to combat the COVID-19 outbreak, with 100 patients who agreed to participate in the study. Personal information form, Beck hopelessness scale and Death anxiety scale were used to collect data. The mean Beck Hopelessness score of the patients was 6.57 +/- 3.085 and the mean Death Anxiety Scale was 9.16 +/- 2.242. There was a statistically significant difference between the mean scores of Beck hopelessness and education level (p = 0.001) and between the mean scores of Beck hopelessness and age (p = 0.037) of patients diagnosed with COVID-19 who are aged 65 and over. In addition, a statistically significant difference was found between the ages of the patients and their mean scores on the death anxiety scale (p = 0.023), and between the mean scores of the death anxiety scale and the condition of having a chronic disease (p = 0.001). In the light of the obtained data, certain social services can be put into practice to reduce/prevent the affection of the epidemic on older adults people.
Keywords: Hopelessness; Death anxiety; Patients at the age of 65; COVID-19; Nursing care